Pengaruh Pelatihan Pblic Speaking terhadap Keaktifian Belajar Peserta Didik pada Mata Pelajaran Pendidikan Agama Islam (PAI) - Imam Maulana; Ahmad Haromaini; Faiz Fikri Al Fahmi (Qiro'ah : Jurnal Pendidikan Agama Islam, 2021)
This research was conducted with the aim of knowing students in the show much influence the public speaking training has on the learning atctiveness of 8th grade students in the subject of islam religious education at SMP Prima Bakti Kecamatan Panongan Kabupaten Tangerang. The research method used is quantitative research methods with data collection techniques in the form of distributing questionnaires. The respondents of this study were 50 students, based on the results of data processing and discussion, it was concluded that the public speaking training had a strong effect of 44,89% on the learning activeness of students in the subject of Islamic religious education and in testing the hypothesis t count>t table means that Ho is rejected and accepted ha